Challenges of Retirees in Aboh Mbaise Local Government Area of Imo State - E. C., Uneze-Amby; U. E., Nnubia (Journal of Home Economics Research, 2024)
This study investigated the challenges of retirement on parents in Aboh Mbaise L.G.A. of Imo State. Specifically it identified challenges retirees face and strategies for coping with those challenges. The population of the study was 1,121 registered retirees as the sample of the study was 375 retirees which comprised 200 male retirees and 175 female retirees from Fifteen (15) communities selected out of the thirty (33) communities. The instrument for data collection was a questionnaire. Data was analysed using the mean. Findings reveal 25 challenges confronting the retirees including; insufficient financial, resources, problem of securing residential accommodation, poor social-economic status, difficult health and challenges of declining health and domestic violence. Other findings are 15 coping strategies which include learning a moderate life style, involvement in religious activities and socialization. Based on the findings the study concludes that Government should ensure that retirees are incorporated in the health insurances, pensions and gratuity should always be paid as and when due and that adequate housing scheme are provided for the workers while they are still in active service.